Oral contraceptives and colorectal cancer risk: a meta-analysis - Fernandez, E (Nature Publishing Group, 2001)
Several studies have suggested an inverse association between use of combined oral contraceptives (OC) and the risk of colorectal cancer and here we present a meta-analysis of published studies. Articles considered were epidemiological studies published as full papers in English up to June 2000 that included quantitative information on OC use. The pooled relative risks (RR) of colorectal cancer for ever OC use from the 8 case-control studies was 0.81 (95% confidence interval (CI): 0.69–0.94), and the pooled estimate from the 4 cohort studies was 0.84 (95% CI: 0.72–0.97). The pooled estimate from all studies combined was 0.82 (95% CI: 0.74–0.92), without apparent heterogeneity. Duration of use was not associated with a decrease in risk, but there was some indication that the apparent protection was stronger for women who had used OCs more recently (RR = 0.46; 95% CI: 0.30–0.71). A better understanding of this potential relation may help informed choice of contraception. © 2001 Cancer Research Campaign http://www.bjcancer.com